Transformational leadership style and knowledge management among university administrators in Malaysia: Examining the moderating effect of organizational structure - Darus, Amer; Sri Ramalu, Subramaniam; Mohd Noor, Noor Azila; Zainal Abidin, Zarina (Serials Publications, 2014)
The study examines the relationships between transformational leadership style, knowledge management and organizational structure using a field study of 255 administrators in one public University in Malaysia. The findings of this study reveal that transformational leadership style is a vital in promoting knowledge management practices in an organization. Specifically, the result of this study reveals that idealized influence, inspirational motivation, intellectual stimulation and individualized consideration of transformational leadership style significantly influence knowledge management practices. Organizational structure found to moderate the effects of transformational leadership on knowledge management indicating that organizational structure plays a crucial role in assisting the leaders to manage knowledge across the organization.The findings of this study have significant contribution to the body of knowledge in the field of knowledge management as well as practical implication to public institutions in Malaysia.